1984
DOI: 10.1002/ana.410160508
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal dendritic abnormalities in a rat model of phenylketonuria

Abstract: An increased concentration of dendritic spines was present in one region of the hippocampus in rats made hyperphenylalaninemic (phenylketonuria model). It is uncertain whether this finding resulted from an actual hyperplasia or a failure of maturational spine reduction. The result is unusual in that Golgi studies of most mental retardation syndromes and relevant animal models have shown loss of dendritic spines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It is the part of the brain with major neurological sensitivity, such that alterations in synthesis, storage, release, or inactivation of the excitatory or inhibitory amino acids could disrupt important neurological functions [Walsh and Emerich, 1988]. In PKU, there is clear evidence of dendritic abnormalities in the hippocampus [Lacey, 1984]. To date, similar neuropathologic studies have not been conducted in maternal PKU.…”
Section: Possible Theoretical Basis For Neuropsychological Effects Inmentioning
confidence: 99%
“…It is the part of the brain with major neurological sensitivity, such that alterations in synthesis, storage, release, or inactivation of the excitatory or inhibitory amino acids could disrupt important neurological functions [Walsh and Emerich, 1988]. In PKU, there is clear evidence of dendritic abnormalities in the hippocampus [Lacey, 1984]. To date, similar neuropathologic studies have not been conducted in maternal PKU.…”
Section: Possible Theoretical Basis For Neuropsychological Effects Inmentioning
confidence: 99%
“…Glushakov et al (10) found that a high concentration of phenylalanine attenuated NMDA-activated currents in cultured hippocampal neurons. In vivo 31 P-MRS demonstrated abnormalities of cerebral energy metabolism in PKU, indicating a link between phenylalanine neurotoxicity and imbalances of cerebral energy metabolism (11). Lately, Horster et al (5) revealed that phenylalanine reduced synaptic density and simultaneously inhibited pyruvate kinase in mixed cortical cultures.…”
mentioning
confidence: 99%
“…Applications of the Golgi methods to the brains of PKU patients,~ and in animal models of PKU, [8][9][10][11][12] have shown alterations of neuronal and dendritic architecture that may account for the retardation and seizures. We have recently studied the brain of a 4month-old child with the maternal PKU syndrome, using routine and Golgi histologic techniques.…”
mentioning
confidence: 99%